Do Regulatory Changes Seriously Affect the Medical Devices Industry? Evidence From the Czech Republic - Maresova, Petra; Rezny, Lukas; Peter, Lukas; Hajek, Ladislav; Lefley, Frank (Frontiers in Public Health, 2021)
Background: Within the EU, some of the challenges and perceived risks now facing medical device (MD) developers result from changes in the regulatory framework with increased emphasis on safety. Medical technology companies are therefore required to adopt stricter quality assurance measures so that individual devices can be speedily tracked and retrieved in case of emergency. Objectives: We highlight the challenges and risks faced by the European medical devices industry and particularly those faced by SMEs in the Czech Republic. We address two important research questions: Q1. Do the benefits from increased regulation outweigh the additional costs? Q2. As a large proportion of MD developers are SMEs, will the new regulatory regime result in some of those companies going out of business and therefore impede future innovation? Methods: The paper focuses on a single case study, with the situation and outcomes discussed in the context of the financial results of a further 50 medical device manufacturers marketing in the Czech Republic. Results: Our findings suggest that the new legislation will result in improved safety, facilitate product recalls, but the cost and administrative burden may be high. The evidence also indicates that some SMEs may be forced to diversify to ‘non-medical’ products, with the inevitable loss of innovative MDs being made available to patients and healthcare providers.